A novel canine model of immune thrombocytopenia: has immune thrombocytopenia (ITP) gone to the dogs?. (8th July 2014) - LeVine, Dana N.; Birkenheuer, Adam J.; Brooks, Marjory B.; Nordone, Shila K.; Bellinger, Dwight A.; Jones, Sam L.; Fischer, Thomas H.; Oglesbee, Stephen E.; Frey, Kahlina; Brinson, Nicole S.; Peters, Allison P.; Marr, Henry S.; et al.
Summary Canine immune thrombocytopenia (ITP) is analogous to human ITP, with similar platelet counts and heterogeneity in bleeding phenotype among affected individuals. With a goal of ultimately investigating this bleeding heterogeneity, a canine model of antibody‐mediated ITP was developed. Infusion of healthy dogs with 2F9, a murine IgG2a monoclonal antibody to the canine platelet glycoprotein GPIIb (a common target of autoantibodies in ITP) resulted in profound, dose‐dependent thrombocytopenia. Model dogs developed variable bleeding phenotypes, e.g. petechiae and haematuria, despite similar degrees of thrombocytopenia. 2F9 infusion was not associated with systemic inflammation, consumptive coagulopathy, or impairment of platelet function. Unexpectedly however, evaluation of cytokine profiles led to the identification of platelets as a potential source of serum interleukin‐8 (IL8) in dogs. This finding was confirmed in humans with ITP, suggesting that platelet IL8 may be a previously unrecognized modulator of platelet‐neutrophil crosstalk. The utility of this model will allow future study of bleeding phenotypic heterogeneity including the role of neutrophils and endothelial cells in ITP.